2023
DOI: 10.3389/fped.2023.1079290
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective validation of G-ROP, CO-ROP, Alex-ROP, and ROPscore predictive algorithms in two Chinese medical centers

Abstract: PurposeTo evaluate the sensitivity and specificity of four predictive algorithms (G-ROP, CO-ROP, Alex-ROP, and ROPscore) for retinopathy of prematurity and compare their performances in the Chinese population.MethodsA retrospective study was conducted at two medical centers in China of infants born at Women's Hospital School of Medicine Zhejiang University and Yiwu Maternal and Child Health Hospital. A total of 1,634 infants who met the criteria and who were GA < 32 weeks or BW < 2,000 g accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…On the other hand, studies from socio‐economically developing countries, such as Egypt, Iran, Thai, and another study from Turkey, reported the sensitivity for treated and Type 1 ROP was 100%, similar to ours (Ahmed et al., 2022; Fadakar et al., 2022; Okbay Gunes et al., 2022; Trinavarat et al., 2023) (Table 2). Furthermore, in a study from China, three severe ROP cases missed by GA and BW criteria were detected by the WG criterion (Lu et al., 2023). The authors noted that WG contributed to detecting severe ROP in infants with a relatively larger BW and older GA (Lu et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, studies from socio‐economically developing countries, such as Egypt, Iran, Thai, and another study from Turkey, reported the sensitivity for treated and Type 1 ROP was 100%, similar to ours (Ahmed et al., 2022; Fadakar et al., 2022; Okbay Gunes et al., 2022; Trinavarat et al., 2023) (Table 2). Furthermore, in a study from China, three severe ROP cases missed by GA and BW criteria were detected by the WG criterion (Lu et al., 2023). The authors noted that WG contributed to detecting severe ROP in infants with a relatively larger BW and older GA (Lu et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study from China, three severe ROP cases missed by GA and BW criteria were detected by the WG criterion (Lu et al., 2023). The authors noted that WG contributed to detecting severe ROP in infants with a relatively larger BW and older GA (Lu et al., 2023). Similarly, in the Egyptian cohort, all infants who developed Type 1 ROP that was not defined by the BW and GA criteria of the G‐ROP model were correctly defined by the WG criterion (Ahmed et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations